Designing The Coal Domestic Market Obligation Competitiveness Policy Through Sustainable Balanced Scorecard and Swot Analysis (Industry Level Analysis of Indonesia) : (Industry Level Analysis of Indonesia) - Ginanjar Maulana (PT. Publikasiku Academic Solution, 2023)
Starting from the problem of government policy regarding DMO on coal, it is important to examine the implications of DMO on the level of competition of the national coal industry in the global market arena. Therefore, the research wants to examine the competitive sources of finance of the national coal industry, and develop strategies to improve sustainable and superior performance so that it can indeed compete in the global market. This approach is qualitative. The research location is the coal industry in Indonesia. The research time is one time, yes it is 2023. Data collection techniques are literature review and document study. Data analysis techniques use the Sustainable Balanced Scorecard (SBSC) model combined with competitive advantage sources, and equipped with SWOT analysis. The results found that the sources of Indonesia's coal competitive advantage are: (i) The.biggest in the industry. (ii) Distance-low transportation cost. (c) Size (large industry size), (d) Strong market share. Then six strategies were proposed to improve sustainable performance in order to compete in the global market. The six strategies are basically a combination of production strengths, coal quality weaknesses, environmental issues, and the development of environmentally friendly technology, as well as technology that can improve coal quality, and can make coal not only for the benefit of energy sources.